Design, optimization and simulation of tradable mobility credits - Liu, Renming (Nanyang Technological University, 2023)
Road traffic congestion is a critical problem affecting urban mobility worldwide and its severity continues to increase, causing significant costs at the individual, environmental, economic, and societal levels. While a significant agenda has been put forward on the transport supply side, mostly driven by vehicle technology (automation and electrification), demand shifts are often considered a hard-to-reach but effective means to reduce the social and environmental costs associated with transport. Demand management has thus become an increasingly important focus of the policy agenda in many metropolitan areas.